What contributes the most to the breast cancer patients’ quality of life during therapy – clinical factors, functional and affective state, or social support? - Novakov, Ivana; Popović-Petrović, Svetlana; Ilinčić-Zlatar, Sonja; Tatić, Milanka; Ševo, Mirjana (Vojnosanitetski pregled, 2021)
Background/Aim. As significant advances in cancer treatment have occurred over the past decades, the crucial questions in oncology nowadays are not related only to the treatment of the illness but also to the quality of life (QOL) of patients. The aim of our study was to explore which set of determinants (clinical, functional, affective, or social) has the greatest impact on explaining QOL in women who live with the diagnosis of breast cancer. Methods. The research was conducted on 64 women (with a mean age of 58.36 ± 11.30) while undergoing radiation therapy at the Oncology Institute of Vojvodina, Serbia. Quality of Life Instrument – Breast Cancer Patient Version (QOL-BC) questionnaire was used for evaluation of physical, psychological, social, spiritual, and general well-being, the Upper Extremity Functional Index (UEFI) was applied for the assessment of the upper extremity function, the Depression, Anxiety, and Stress Scale-21 Items (DASS-21) was used for measuring symptoms of depression, anxiety, and stress, the Medical Outcomes Survey, Social Support Survey (MOS-SSS) served for evaluation of social support; demographic and clinical data of patients were also collected. Results. Analysis of Variance (ANOVA) with repeated measures [F(2.03, 127.80) = 20.24, p
Keywords: breast neoplasms; drug therapy; neoadjuvant therapy; psychology; social support; quality of life; radiotherapy; surveys and questionnaires